Acute Kidney Injury Definition and In‐Hospital Mortality in Patients Undergoing Primary Percutaneous Coronary Intervention for ST‐Segment Elevation Myocardial Infarction. Issue 7 (6th July 2016) - Marenzi, Giancarlo; Cosentino, Nicola; Moltrasio, Marco; Rubino, Mara; Crimi, Gabriele; Buratti, Stefano; Grazi, Marco; Milazzo, Valentina; Somaschini, Alberto; Camporotondo, Rita; Cornara, Stefano; De Metrio, Monica; et al.
Abstract : Background: Acute kidney injury (AKI) has been associated with increased mortality in ST‐segment elevation myocardial infarction. We compared the mortality predictive accuracy of the 3 AKI definitions used most widely for patients with ST‐segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. Methods and Results: We included 3771 patients with ST‐segment elevation myocardial infarction treated with primary percutaneous coronary intervention at 2 Italian hospitals. AKI incidence was evaluated according to creatinine increases of ≥25% (AKI‐25), ≥0.3 mg/dL (AKI‐0.3), and ≥0.5 mg/dL (AKI‐0.5). The primary end point was in‐hospital mortality. Overall, 557 (15%), 522 (14%), and 270 (7%) patients developed AKI‐25, AKI‐0.3, and AKI‐0.5, respectively ( P <0.01). All AKI definitions independently predicted in‐hospital mortality (adjusted odds ratio 4.9 [95% CI 3.1–7.8], 5.4 [95% CI 3.3–8.6], and 8.3 [95% CI 5.1–13.3], respectively; P <0.01 for all). At receiver operating characteristic analysis, the addition of each AKI definition to combined clinical predictors of mortality (age, sex, left ventricular ejection fraction, admission creatinine, creatine kinase‐MB peak) found at stepwise analysis significantly improved mortality prognostication (area under the curve increased from 0.89 for clinical predictor combination alone to 0.92 for AKI‐25, 0.92 for AKI‐0.3, and 0.93 for AKI‐0.5; P <0.01 for all). At reclassification analysis, AKI‐0.5 added to clinical predictors, provided the highest score in mortality (net reclassification improvement +10% versus AKI‐0.3 [ P =0.01] and +8% versus AKI‐25 [ P =0.05]). Conclusions: Each AKI definition significantly improved the mortality prediction beyond major clinical variables. AKI‐0.5 showed a mortality discrimination advantage, suggesting it should be the preferred definition in studies addressing ST‐segment elevation myocardial infarction and focusing on short‐term mortality.